Eosinophilic myocarditis: characteristics, diagnostics and outcomes of a rare condition. Issue 9 (16th September 2016) - Wang, T. K. M.; Watson, T.; Pemberton, J.; Pemberton, L.; Lowe, B.; Ellis, C.; Kingston, N.; Ruygrok, P.
Abstract : Eosinophilic myocarditis is a rare and potentially fatal condition characterised by eosinophilic inflammatory infiltration of myocardium. We report seven consecutive cases of eosinophilic myocarditis at our centre and discuss the important characteristics, investigation and management of this disease.